2005
DOI: 10.1128/mcb.25.10.4105-4116.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Docking Protein FRS2α Is an Essential Component of Multiple Fibroblast Growth Factor Responses during Early Mouse Development

Abstract: The docking protein FRS2␣ is a major mediator of fibroblast growth factor (FGF) signaling. However, the physiological role of FRS2␣ in vivo remains unknown. In this report, we show that Frs2␣-null mouse embryos have a defect in anterior-posterior (A-P) axis formation and are developmentally retarded, resulting in embryonic lethality by embryonic day 8. We demonstrate that FRS2␣ is essential for the maintenance of self-renewing trophoblast stem (TS) cells in response to FGF4 in the extraembryonic ectoderm (ExE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
75
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 55 publications
5
75
0
Order By: Relevance
“…FGF4 produced by the epiblast regulates the proliferation and maintenance of trophoblast stem cells (36). FGFR2 (37), the main FGFR in these cells, and its downstream adaptor molecule FRS2␣ (38) are essential for trophoblast stem cell renewal. FRS2␣, in particular, is required for full-fledged ERK activation in the extraembryonic ectoderm.…”
Section: Resultsmentioning
confidence: 99%
“…FGF4 produced by the epiblast regulates the proliferation and maintenance of trophoblast stem cells (36). FGFR2 (37), the main FGFR in these cells, and its downstream adaptor molecule FRS2␣ (38) are essential for trophoblast stem cell renewal. FRS2␣, in particular, is required for full-fledged ERK activation in the extraembryonic ectoderm.…”
Section: Resultsmentioning
confidence: 99%
“…Northern blotting RNA from mouse brain and NIH3T3 cells were prepared using a standard method (Gotoh et al, 2005). Probes for mouse Frs2a and Frs2b were previously described (Gotoh et al, 2004b).…”
Section: Co-immunoprecipitation Assaysmentioning
confidence: 99%
“…It has been reported that SNT-1/FRS2a mediates multiple FGF-induced cellular responses, including stimulation of the Ras/ERK cascade and activation of phosphatidylinositol (PI)-3 kinase Ong et al, 2001). Snt-1/Frs2a-null mouse embryos show early embryonic lethality due to defects in multiple FGF responses during development, indicating that SNT-1/ FRS2a is essential for FGF signaling in vivo (Gotoh et al, 2005). Ectopic expression of SNT-2/FRS2b in Snt-1/Frs2a À/À mouse embryonic fibroblasts (MEFs) compensates for the loss of SNT-1/FRS2a in activation of ERK in response to FGF, indicating that SNT-1/ FRS2a and SNT-2/FRS2b have redundant roles in FGF signaling (Gotoh et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of the Frs2␣ gene results in early embryonic lethality due to multiple defects in FGF signaling, such as defects in trophoblast stem cells that self-renew in the presence of FGF4 and defects in cell movement through the primitive streak during gastrulation (23). To elucidate the signaling pathways emanating from the Shp2-binding sites and Grb2-binding sites of FRS2␣, we generated mice carrying mutations of either the two tyrosine residues that act as the Shp2-binding sites (Frs2␣ 2F ) or the four tyrosine residues serving as the Grb2 binding sites (Frs2␣ 4F ).…”
mentioning
confidence: 99%